Analysis of Students’ Interest in The Use of National Streaming Service - Hasbi, Imanuddin; Wahyu Nugraha, Diki; Pradana, Mahir (IJORER : International Journal of Recent Educational Research, 2025)
Objective: This study explores Generation Alpha and Z’s inclination to utilize national streaming services through the lens of the Theory of Planned Behavior (TPB). It aims to examine how attitudes, subjective norms, and perceived behavioral control shape their intention to use these platforms. Methods: A quantitative research approach was employed, collecting data from a diverse sample of Generation Z individuals. The study measured their attitudes towards national streaming services, the influence of social norms, and their perceived control over using these platforms. Results: The findings indicate that positive attitudes, particularly regarding content diversity and affordability, significantly drive user interest. Additionally, subjective norms and perceived behavioral control also play crucial roles in shaping intentions to adopt national streaming services. Novelty: This research contributes to the understanding of digital media consumption behavior among younger generations, offering insights for national streaming service providers to better engage Generation Alpha and Z through targeted strategies aligned with behavioral drivers.